Urine neopterin as a parameter of disease activity in patients with systemic lupus erythematosus: comparisons with serum sIL-2R and antibodies to dsDNA, erythrocyte sedimentation rate, and plasma C3, C4, and C3 degradation products. Issue 6 (June 1993) - Lim, K L; Jones, A C; Brown, N S; Powell, R J
Abstract : OBJECTIVES--To investigate urine neopterin as a parameter of disease activity in an unselected group of patients with systemic lupus erythematosus (SLE) and to study the relation between urine neopterin and certain patterns of organ disease and differing drug regimens in the treatment of SLE. METHODS--Neopterin was determined by high performance liquid chromatography in 115 early morning urine samples from 68 patients with SLE. Serum soluble interleukin 2 receptor (sIL-2R) and antibodies to double stranded DNA (dsDNA) were determined by enzyme linked immunosorbent assay (ELISA), and the erythrocyte sedimentation rate (ESR), plasma C3, C4, and C3 degradation products (C3dg) were measured in corresponding blood samples. Disease activity was scored using the British Isles Lupus Assessment Group (BILAG) index. RESULTS--Urine neopterin was significantly increased in patients with active and inactive SLE compared with the control group and was significantly higher in patients with active than in those with inactive SLE. Urine neopterin did not distinguish between subsets of patients with SLE with particular patterns of organ disease, as defined by the BILAG index, nor was its level primarily influenced by differing drug regimens. Levels of serum sIL-2R, antibodies to dsDNA, the ESR, and plasma C3, C4, and C3dg were also significantly different between the patients with active and inactive SLE. Unlike urine neopterin there was considerable overlap in the values of these parameters between the two activity groups. Highly significant correlations found between urine neopterin and serum sIL-2R, ESR, and plasma C3, C4, and C3dg suggest the close association of neopterin with clinical activity in SLE. Multivariate logistic regression analysis showed that urine neopterin > 300 mumol/mol creatinine was a highly significant predictor of disease activity with an odds ratio of 3.51. CONCLUSIONS--Determination of urine neopterin, a non-invasive, relatively simple and inexpensive measurement, appears to be the best parameter for assessing and monitoring disease activity and treatment in patients with SLE.